Agressividade na primeira infância: um estudo a partir das relações estabelecidas pelas crianças no ambiente familiar e na creche - Iza Rodrigues da Luz (2005)
Drawing on Winnicott, Erikson and other researchers of early childhood education and sociology. This dissertation aims at investigating aggressiveness in early childhood based on the relationships established by children within their families and educational institutions. Data was collected in an early child care center in order to a) analyze modes of acting of aggressive and non-aggressive children interacting with their mothers and the researcher while performing activities scheduled at the day care center; b) get acquainted with the life histories of aggressive children and their relationships with their mothers and the researcher; c) compare data on aggressive and non- aggressive children so as to have an insight into aggressiveness manifestation from the perspective of the relationships established by those children at home and in the day care institution. An empirical study was carried out in three phases: first, the researcher observed the daily routine of the day care center, selected the children to be subjects for the study and interviewed the centers supervisor and four teachers to learn about their views on aggressiveness, violence and discipline and how those conditions should be dealt with; second, the children selected as subjects both aggressive and non- aggressive children were videotaped during their performance of tasks at the center and their interaction with their mothers and the researcher; third, teachers, assistants and family members of the subjects were interviewed. Results point to a correlation between the family setting dynamics and the way children express aggressiveness. Children considered to be aggressive within the day care setting proved not to be able to rely on their family setting to develop a sense of self-assurance so as to deal with their destructive capacity within that setting. Aggressiveness emerging at the day care center was understood as an attempt for seeking self-assurance lacking in the family setting. Non-aggressive children managed to feel at ease in order to express aggressiveness at home and behave in a way suitable to the day care center expectations, that is to say, they managed to control their bodily movements and obey to the teachers directions. From the perspective of early childhood institutions policies to promote the development of children so as to complement family actions, it was observed that regarding aggressive as well as non-aggressive children the day care center did not have strategies for particular interventions that could help those children develop capacities and skills little developed at home. This points to the need for further research on aggressiveness that may lead us to better understand the kind of relationship between children and care providers which allows for childrens expression of aggressiveness. Further studies are also needed on the way early childhood educational centers operate in order to promote pedagogical projects aiming at the development of children taking into account their individual necessities and profiles.